2018
DOI: 10.1186/s40635-018-0203-4
|View full text |Cite
|
Sign up to set email alerts
|

Tight junction structure, function, and assessment in the critically ill: a systematic review

Abstract: BackgroundEpithelial and endothelial barrier integrity, essential for homeostasis, is maintained by cellular boarder structures known as tight junctions (TJs). In critical illness, TJs may become disrupted, resulting in barrier dysfunction manifesting as capillary leak, pulmonary edema, gut bacterial translocation, and multiple organ failure. We aim to provide a clinically focused overview of TJ structure and function and systematically review and analyze all studies assessing markers of endothelial and epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 68 publications
0
63
0
11
Order By: Relevance
“…Vascular endothelium serves as a first line of defense against injury to blood vessels and the underlying tissues. Endothelium functions as a barrier and dynamically regulates the exchanges of substances between blood stream and the blood vessel wall; dysfunction of endothelial barrier may increase infiltration of blood proteins, toxic agents and immune cells into the vessel wall, resulting in various diseases [7]. The endothelial barrier function is achieved by a transcellular system and coordinated opening and closure of cell-cell junctions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular endothelium serves as a first line of defense against injury to blood vessels and the underlying tissues. Endothelium functions as a barrier and dynamically regulates the exchanges of substances between blood stream and the blood vessel wall; dysfunction of endothelial barrier may increase infiltration of blood proteins, toxic agents and immune cells into the vessel wall, resulting in various diseases [7]. The endothelial barrier function is achieved by a transcellular system and coordinated opening and closure of cell-cell junctions [8].…”
Section: Introductionmentioning
confidence: 99%
“…The main functions of occludin are regulation and sealing of TJs [41,42]. That ZO-1 outperformed other TJ markers may re ect the concomitant organ epithelial injury which occurs in MODS [36]. Therefore, we observed the expression of the above two proteins at 24 and 48 h in the three groups, and the results showed that occludin and ZO-1 in the CLP group were signi cantly lower than those in the Sham group and the FMT group.…”
Section: Discussionmentioning
confidence: 86%
“…Tight junctions play an important role in maintaining the integrity of the mucosal epithelium [34,35], and it is generally de ned as life-threatening organ failure in the setting of critical illness [36,37]. The barrier function is mediated by changes in the tight junctions and associated proteins and allows out ow of luminal contents and likely damages distant organs, which may contribute to MODS [12].…”
Section: Discussionmentioning
confidence: 99%
“…CLDNs are integral components of TJs, and its membrane expression maintain paracellular permeability and are critical for epithelial cell polarity. 19 It is revealed that the change of expression level and localization of CLDNs was an important cause of tumor development. 29,30 For example, a concurrent cytoplasmic subcellular location of CLDN1 expression is associated with malignant canine thyroid tumors and their vascular invasion thyroid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, CLDNs are integral membrane proteins localized at tight junctions, which are responsible for establishing and maintaining epithelial cell polarity and it is accepted that the CLDNs are low expressed in the mesenchymal cells. [17][18][19] At present, there are also several literatures on CLDNs in sarcomas. For instance, the expression of CLDN4, −7 and 10 were found expressed in biphasic synovial sarcomas, and CLDN1 expression was also identified in 63% of Ewing's sarcoma family tumors.…”
Section: Introductionmentioning
confidence: 99%